The soul of Judaism : Jews of African descent in America - Haynes, Bruce D., 1960- (Religion, race, and ethnicity, 2018)
Explores the full diversity of Black Jews, including bi-racial Jews of both matrilineal and patrilineal descent; adoptees; black converts to Judaism; and Black Hebrews and Israelites, who trace their Jewish roots to Africa and challenge the dominant western paradigm of Jews as white and of European descent. The book showcases the lives of Black Jews, demonstrating that racial ascription has been shaping Jewish selfhood for centuries. It reassesses the boundaries between race and ethnicity, offering insight into how ethnicity can be understood only in relation to racialization and the one-drop rule. Within this context, Black Jewish individuals strive to assert their dual identities and find acceptance within their communities. Putting to rest the notion that Jews are white and the Black Jews are therefore a contradiction, the volume argues that we cannot pigeonhole Black Hebrews and Israelites as exotic, militant, and nationalistic sects outside the boundaries of mainstream Jewish thought and community life. it spurs us to consider the significance of the growing population of self-identified Black Jews and its implications for the future of American Jewry.